2021
DOI: 10.1111/avsc.12598
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the ground vegetation in spruce forests in the Erzgebirge (Ore Mountains) — bryophytes are better indicators of the impact of liming and of sulphur and nitrogen deposition than the herb layer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
(87 reference statements)
2
7
0
Order By: Relevance
“…The lack of significant variations in bryophyte species richness in Polish forests seems at first to supports the results by Dittrich et al (2016), reporting no trends in overall species richness over a century, and to contrast with those by Becker-Scarpitta et al (2017), who observed an increase in species richness over a 30-year time span, as well as with those by the above mentioned study by Baumann et al (2021), also reporting a diversity increase in ground bryophytes. However, in our study we pooled and examined together both coniferous and broadleaved forests, while Dittrich et al (2016) andBecker-Scarpitta et al (2017) examined just broadleaved forests and Baumann et al (2021) just coniferous ones.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The lack of significant variations in bryophyte species richness in Polish forests seems at first to supports the results by Dittrich et al (2016), reporting no trends in overall species richness over a century, and to contrast with those by Becker-Scarpitta et al (2017), who observed an increase in species richness over a 30-year time span, as well as with those by the above mentioned study by Baumann et al (2021), also reporting a diversity increase in ground bryophytes. However, in our study we pooled and examined together both coniferous and broadleaved forests, while Dittrich et al (2016) andBecker-Scarpitta et al (2017) examined just broadleaved forests and Baumann et al (2021) just coniferous ones.…”
Section: Discussionsupporting
confidence: 77%
“…However, as in the case of forest management practices, the pollution drop was not enough to ultimately determine an increase of bryophyte diversity. Meanwhile, Baumann et al (2021) ascribed the observed increase in bryophyte species richness and cover in the spruce forests of eastern Germany just to the sharp decline in S deposition. These contrasting conclusions may be accounted for by the difference in the scale of observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some articles published in 2021 focused on traditional species‐level analyses of vegetation change (e.g. Baumann et al, 2021), but others also conducted phylogenetic analyses of vegetation change, such as Santo‐Silva et al (2021), who found phylogenetic homogenization of tree assemblages in isolated forest patches in the Amazon.…”
Section: Network and Topics In The Journalmentioning
confidence: 99%